EFEKTIVITAS PELAKSANAAN PROGRAM KAMPUNG IKLIM (PROKLIM) DI DESA POLEONRO KECAMATAN LAMURU KABUPATEN BONE PROVINSI SULAWESI SELATAN - Sudarwanto Sudarwanto; Amir Tjoneng; Suriyanti Suriyanti (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
This study aims 1). Analyzing the effectiveness of the implementation of the Village Climate Program activities in Poleonro Village; 2). Analyzing the level of community participation in the implementation of the Climate Village Program in Poleonro Village; 3). Analyzing the relationship between the socio-economic factors of the community on the level of community participation in the Climate Village Program (PROKLIM) in Poleonro Village.The research was conducted in Poleonro Village, Lamuru District, Bone Regency, South Sulawesi Province. Field data collection, data processing, and analysis, as well as thesis preparation, took place from February to August 2020. The method used in this research was a descriptive method with interviews, questionnaires, observation, and documentation. Data analysis used a descriptive qualitative analysis and multiple linear regression.The results showed that the implementation of the Climate Village Program (PROKLIM) in Poleonro Village was classified as effective. This result according to the activity component of the Climate Village Program (PROKLIM) which had carried out climate change adaptation activities were 70.12%, climate change mitigation activities were 60.06%, and group activities of community and support for sustainability were 72.77%. The level of community participation in the implementation of the Climate Village Program (PROKLIM) activities in Poleonro Village for climate change adaptation, climate change mitigation, group activities of community and support for the sustainability of the level of participation was high. The level of education and counseling has a positive relationship with PROKLIM activities, while the variables age and income level have a negative relationship with the level of participation.